The Effect of Module-Based Bounded Inquiry Laboratory on the Digestive System Material of Xi Grade toward Process Dimension of Studentsâ Science Literacy - *, Suciati; Hermita, Resty (Proceeding of International Conference on Teacher Training and Education, 2016)
The purpose of this study is find out the effect of module-based bounded inquiry laboratory on the digestivesystem material of XI grade toward process dimension of studentsâ science literacy. This study was quasiexperimental research used the one group pretest-posttest design. The population of this study was allstudents of 7th State Senior High School Surakarta. The sample was taken using 28 students in XI grade ofscience class first. The data was collected through test and non-test techniques. Data analyzed by usingnormalized N-gain and Wilcoxon test. The result of study showed module-based bounded inquirylaboratory on the digestive system material of XI grade was influenced toward process dimension ofstudentsâ science literacy by Wilcoxon test evidenced p < 0,05, Ho are ignored. Therefore, it is significantdifference of the result before (44,22) and after (83,51) the using module. Based on the results of the studycan be concluded that there is significant effect of module-based bounded inquiry laboratory on thedigestive system material of XI grade toward process dimension of studentsâ science literacy.